Magnetic separation of peripheral nerve-resident cells underscores key molecular features of human Schwann cells and fibroblasts: an immunochemical and transcriptomics approach - Peng, Kaiwen (2020)
Nerve-derived human Schwann cell (SC) cultures are irreplaceable models for basic and translational research but their use can be limited due to the risk of fibroblast overgrowth. Fibroblasts are an ill-defined population consisting of highly proliferative cells that, contrary to human SCs, do not undergo senescence in culture. We initiated this study by performing an exhaustive immunological and functional characterization of adult nerve-derived human SCs and fibroblasts to reveal their properties and optimize a protocol of magnetic-activated cell sorting (MACS) to separate them effectively both as viable and biologically competent cells. We next used immunofluorescence microscopy imaging, flow cytometry analysis and next generation RNA sequencing (RNA-seq) to unambiguously characterize the post-MACS cell products. High resolution transcriptome profiling revealed the identity of key lineage-specific transcripts and the clearly distinct neural crest and mesenchymal origin of human SCs and fibroblasts, respectively. Our analysis underscored a progenitor- or stem cell-like molecular phenotype in SCs and fibroblasts and the heterogeneity of the fibroblast populations. In addition, pathway analysis of RNA-seq data highlighted putative bidirectional networks of fibroblast-to-SC signaling that predict a complementary, yet seemingly independent contribution of SCs and fibroblasts to nerve regeneration. In sum, combining MACS with immunochemical and transcriptomics approaches provides an ideal workflow to exhaustively assess the identity, the stage of differentiation and functional features of highly purified cells from human peripheral nerve tissues.